Self-Review As a Method to Mitigate Recency Effect in Long-Series Audit Information - Aritha Chintya Dewi; Intiyas Utami; Aprina Nugrahesty Sulistya Hapsari (The Indonesian Journal of Accounting Research, 2018)
Abstract: This study aims to analyze the causal relationship between the sequence of information and presentation format of long-series information and self-review method with audit decisions. Our independent variables are the sequence of information, the format of information presentation and self-review method. Meanwhile, our dependent variable is audit decisions. This research uses 75 bachelor students majoring in accounting from Satya Wacana Christian University. We run the paired-sample t-test to test our hypotheses. Our results show that; 1) there is an order effect in individuals' decision-making before they perform self-review if the long-series information is presented sequentially, 2) simultaneous presentation of information mitigates recency effect even before self-review, 3) decisions based on simultaneous information presentation are better than decisions based on sequential information presentation.Abstrak: Penelitian ini bertujuan untuk menganalisis informasi dan metode self-review dengan keputusan audit. Variabel independen kami adalah urutan informasi, format penyajian informasi dan metode self-review. Sementara itu, variabel dependen kami adalah keputusan audit. Penelitian ini menggunakan 75 mahasiswa sarjana jurusan akuntansi dari Universitas Kristen Satya Wacana. Kami menjalankan uji t-paired-sample untuk menguji hipotesis kami. Hasil kami menunjukkan bahwa; 1) ada efek order dalam pengambilan keputusan individu sebelum mereka melakukan self-review jika informasi seri panjang disajikan secara berurutan, 2) penyajian informasi secara simultan mengurangi efek rekonsiliasi bahkan sebelum self-review 3) keputusan berdasarkan presentasi informasi simultan lebih baik daripada keputusan berdasarkan presentasi informasi sekuensial.